An improved lift model for Euler-Lagrange simulations of bubble columns. (16th January 2023) - Subburaj, Rahul; Tang, Yali; Deen, Niels G.
Graphical abstract: Highlights: Different lift models are tested for bubble columns with different aspect ratios. An improved lift model is proposed that varies with local gas fraction and vorticity. The lift model is successfully demonstrated for three different bubble columns. Abstract: The objective of this work is to establish a lift model which can account for the variation in the bubble spreading mechanism with different column aspect ratios. To this end, a strategic approach has been developed and applied to explore the dependency of the lift variation with local flow variables. Numerical simulations are performed by using Computational Fluid Dynamics - Discrete Particle Method (CFD-DPM) coupled with Volume of Fluid (VOF) method in the open-source framework OpenFOAM. Both homogeneous and heterogeneous bubbly flows are considered with the results from reported experiments in literature. It has been found that the local gas fraction and the vorticity are strongly correlated with the lift coefficient. However, using one of these two variables alone cannot describe the lift variation within the bubble columns. Finally, a unified lift model is established that depends on both local gas fraction and vorticity. Euler–Lagrange simulations using this lift model are demonstrated to provide excellent agreement on the bubbly dynamics with experiments of homogeneous bubbly flows and bubble swarms.